As políticas industriais e a evolução da estrutura e do desempenho do setor automobilístico brasileiro: uma análise para o período de 1990 a 2020 - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The automobile industry in Brazil has great representation in the country's economy and development. Given this understanding, we seek to understand the entire historical context of the sector between 1990 and 2020, the period related to its creation, formation, and evolution to the present day. In addition, expose industrial policies to encourage the automotive industry and identify possible changes in the structure and performance of the sector throughout its trajectory in the country. The methodological procedures included surveys, selection and reading of books, scientific articles, theses, dissertations and sectorial studies, as well as primary data collection in magazines, newspapers, and secondary data collection with ANFAVEA, IBGE, IPEA and PIA. Afterwards, analyze the functioning of the sector through specific variables of structure, performance, Market Share and concentration indices. As main results, we note that the national automotive sector managed to consolidate its structures and develop its industrial activities, and part of this development was linked to the effects of targeted industrial policies, which contributed to regional deconcentration of companies and industrial units, and increased competition for market among automakers. Therefore, car assemblers do not only depend on specific policies aimed at the sector to achieve certain results, but also on a stable Brazilian and international scenario to achieve good results.
Keywords: Indústria automobilística brasileira; Políticas industrias; Estrutura; Desempenho; Brazilian automotive industry; Industrial policies; Structure; Performance; CNPQ::CIENCIAS SOCIAIS APLICADAS